Populations of Flavalona setigera (Brehm, 1931) in Brazil belong to a new species : Flavalona asymmetrica (Cladocera: Chydoridae: Aloninae) - Sousa, Francisco Diogo Rocha (2018)
Flavalona asymmetrica sp. nov. belongs to the costata-clade. This species has two main head pores, a feature shared only with Flavalona setigera (Brehm, 1931). Morphological differences between them are related to main and lateral head pores, armature of scrapers on the second limb, and proportion of setae on the third and fourth limbs, number of denticles on the postabdomen. Males of F. asymmetrica sp. nov. has genital process about ten times shorter than length of postabdominal claw, which is an exclusive morphological trait. Flavalona asymmetrica sp. nov. is a Neotropical species, so far, it occurs only in Brazil and can be found together with Flavalona iheringula (Sinev & Kotov, 2004) and Flavalona margipluma (Sousa, Santos, Güntzel, Diniz-Filho, de Melo-Júnior & Elmoor-Loureiro, 2015).